CULTURE OF CALLUS OF Hedera canariensis, WILLD - Robbins, William J. (1969)
Callus from stems of adult Hedera canariensis has been maintained on synthetic media for 29 successive passages over a period of three years. Callus from petioles of adult H. canariensis and from cotyledons has also been grown in culture.